2021
DOI: 10.1007/s11625-021-00925-y
|View full text |Cite
|
Sign up to set email alerts
|

Four propositions on integrated sustainability: toward a theoretical framework to understand the environment, peace, and sustainability nexus

Abstract: The sustainability agenda has evolved around a set of interconnected dilemmas regarding economic, social, and environmental goals. Progress has been made in establishing thresholds and targets that must be achieved to enable life to continue to thrive on the planet. However, much work remains to be done in articulating coherent theoretical frameworks that adequately describe the mechanisms through which sustainability outcomes are achieved. This paper reviews core concepts in the sustainability agenda to devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Another study anchored on positive peace is Nicoson’s (2021) theorization on how peace can be aligned with degrowth processes of redistribution, reprioritized care economies, and global equity to address social and economic structural issues driving climate change and exacerbating climate impacts. In a country-level study, Fisher et al (2021) presented a composite index of peace, environment, and sustainability and found that countries with cooperation-enabling institutions are more likely to provide basic human needs, promote individual freedoms, and address generational equity while meeting economic, political, social, and environmental sustainability goals. As Simangan et al (2021) argue, these aspects of sustainability fit within the framing of positive peace.…”
Section: Localizing Positive Peace and Environmental Sustainabilitymentioning
confidence: 99%
“…Another study anchored on positive peace is Nicoson’s (2021) theorization on how peace can be aligned with degrowth processes of redistribution, reprioritized care economies, and global equity to address social and economic structural issues driving climate change and exacerbating climate impacts. In a country-level study, Fisher et al (2021) presented a composite index of peace, environment, and sustainability and found that countries with cooperation-enabling institutions are more likely to provide basic human needs, promote individual freedoms, and address generational equity while meeting economic, political, social, and environmental sustainability goals. As Simangan et al (2021) argue, these aspects of sustainability fit within the framing of positive peace.…”
Section: Localizing Positive Peace and Environmental Sustainabilitymentioning
confidence: 99%
“…Therefore, especially as business models evolve towards QBL pillars, explicitly integrating SDGs in those pillars in ways that such vital factors as preserving culture, maintaining peace, and creating a just society should not be ignored. Although it is harder to quantify and measure the progress of those factors, developing integrative frameworks such as Fisher et al [114] describe is the first step towards building more inclusive and equitable decision-making processes.…”
Section: Discussionmentioning
confidence: 99%
“…Their review results show that while climate change can intensify conflicts, factors such as the presence of strong institutions can provide opportunities for peacebuilding and cooperation between communities affected by climate change impacts. The significance of promoting cooperation has also been highlighted by Fisher et al ( 2021 ). They show that countries with cooperation-enabling institutions have a better performance in terms of achieving integrated sustainability indicators.…”
mentioning
confidence: 89%